2012
DOI: 10.1016/j.ccr.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

KrasG12D-Induced IKK2/β/NF-κB Activation by IL-1α and p62 Feedforward Loops Is Required for Development of Pancreatic Ductal Adenocarcinoma

Abstract: SUMMARY Constitutive Kras and NF-κB activation is identified as signature alterations in pancreatic ductal adenocarcinoma (PDAC). However, how NF-κB is activated in PDAC is not yet understood. Here, we report that pancreas-targeted IKK2/β inactivation inhibited NF-κB activation and PDAC development in KrasG12D and KrasG12D;Ink4a/ArfF/F mice, demonstrating a mechanistic link between IKK2/β and KrasG12D in PDAC inception. Our findings reveal that KrasG12D-activated AP-1 induces IL-1α, which, in turn, activates N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
455
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 454 publications
(480 citation statements)
references
References 41 publications
15
455
0
2
Order By: Relevance
“…1,3,4,47 This suggests that NF-kB-mediated p62/SQSTM1 upregulation may represent a feed-forward signal for prolongation of NF-kB activity and thus cell survival during granulocytic maturation. In line with this assumption, Ling et al 51 showed that the NF-kB pathway is activated by Kras (G12D) in pancreatic ductal adenocarcinoma through p62/SQSTM1 and IL-1 alpha feed-forward loops. In fact, the mutual regulation between p62/SQSTM1 and NF-kB pathways warrants further investigation.…”
Section: Discussionmentioning
confidence: 91%
“…1,3,4,47 This suggests that NF-kB-mediated p62/SQSTM1 upregulation may represent a feed-forward signal for prolongation of NF-kB activity and thus cell survival during granulocytic maturation. In line with this assumption, Ling et al 51 showed that the NF-kB pathway is activated by Kras (G12D) in pancreatic ductal adenocarcinoma through p62/SQSTM1 and IL-1 alpha feed-forward loops. In fact, the mutual regulation between p62/SQSTM1 and NF-kB pathways warrants further investigation.…”
Section: Discussionmentioning
confidence: 91%
“…3B). During writing up of this study, Ling et al reported that IKK␤ activation is required for p62 expression during the development of pancreatic ductal adenocarcinoma (29). Further, there was attenuated mTOR activation caused by p50 deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47][48] IL-1 has already been described to induce CCL22 expression. 6 Our data suggest a novel role of tumor cell-derived IL-1a, mediating CCL22 induction in immune cells and thus fostering the formation of an immunosuppressive micromilieu.…”
Section: Discussionmentioning
confidence: 99%